A history of loss of consciousness or post-traumatic amnesia in minor head injury: "conditio sine qua non" or one of the risk factors?. Issue 12 (30th April 2007) - Smits, M; Hunink, M G M; Nederkoorn, P J; Dekker, H M; Vos, P E; Kool, D R; Hofman, P A M; Twijnstra, A; de Haan, G G; Tanghe, H L J; Dippel, D W J
Abstract : Objective: A history of loss of consciousness (LOC) or post-traumatic amnesia (PTA) is commonly considered a prerequisite for minor head injury (MHI), although neurocranial complications also occur when LOC/PTA are absent, particularly in the presence of other risk factors. The purpose of this study was to evaluate whether known risk factors for complications after MHI in the absence of LOC/PTA have the same predictive value as when LOC/PTA are present. Methods: A prospective multicentre study was performed in four university hospitals between February 2002 and August 2004 of consecutive blunt head injury patients (⩾16 years) presenting with a normal level of consciousness and a risk factor. Outcome measures were any neurocranial traumatic CT finding and neurosurgical intervention. Common odds ratios (OR) were estimated for each of the risk factors and tested for homogeneity. Results: 2462 patients were included: 1708 with and 754 without LOC/PTA. Neurocranial traumatic findings on CT were present in 7.5% and were more common when LOC/PTA was present (8.7%). Neurosurgical intervention was required in 0.4%, irrespective of the presence of LOC/PTA. ORs were comparable across the two subgroups (p>0.05), except for clinical evidence of a skull fracture, with high ORs both when LOC/PTA was present (OR = 37, 95% CI 17 to 80) or absent (OR = 6.9, 95% CI 1.8 to 27). LOC and PTA had significant ORs of 1.9 (95% CI 1.0 to 2.7) and 1.7 (95% CI 1.3 to 2.3), respectively. Conclusion: Known risk factors have comparable ORs in MHI patients with or without LOC or PTA. MHI patients without LOC or PTA need to be explicitly considered in clinical guidelines.